The Influence of Midjourney AI on Animation Character Design: A Case Study of Multimedia Design Students at The University of Jordan - Khasawneh, Fuad; Al-Shboul, Muhannad; Al-Saaideh, Ra'ed (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study aimed to reveal the influence of teaching using the Midjourney artificial intelligence (AI)-based intelligence platform on developing the animation character design skills among students of the multimedia design course at the University of Jordan. The study used a quasi-experimental methodology with a sample of 60 male and female students of the Multimedia Design course from the Department of Visual Arts at the University of Jordan. The study participants were intentionally chosen and randomly divided into two groups: the experimental group, which consisted of 32 male and female students who utilized the educational application based on AI Midjourney, and the control group, which consisted of 28 male and female students who used the conventional method of studying. The findings indicated that there were statistically significant differences, at a significance level of (α = 0.05), in the average scores of the two groups regarding their post-performance in animation character design skills. The experimental group, which utilized the AI-based application Midjourney as a teaching method, demonstrated superior performance compared to the control group.